How to read a Japanese poem - Carter, Steven D. 1950- (Columbia University Press, 2019)
Ancient song and poetry -- Long poems and short poems -- Popular song -- Linked verse -- Unorthodox poems -- Comic poems -- Poems in Chinese
Includes bibliographical references and index
Keywords: Geschichte; Klassisches Japanisch; Lyrik; Japanisch; Kanshi; Japanese poetry / History and criticism; Japanese poetry / Appreciation; Anthologie